2007
DOI: 10.4049/jimmunol.179.12.8533
|View full text |Cite
|
Sign up to set email alerts
|

The Required Role of Endogenously Produced Lipoxin A4 and Annexin-1 for the Production of IL-10 and Inflammatory Hyporesponsiveness in Mice

Abstract: The appropriate development of an inflammatory response is central for the ability of a host to deal with any infectious insult. However, excessive, misplaced, or uncontrolled inflammation may lead to acute or chronic diseases. The microbiota plays an important role in the control of inflammatory responsiveness. In this study, we investigated the role of lipoxin A4 and annexin-1 for the IL-10-dependent inflammatory hyporesponsiveness observed in germfree mice. Administration of a 15-epi-lipoxin A4 analog or an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
114
0
5

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 122 publications
(129 citation statements)
references
References 62 publications
(82 reference statements)
10
114
0
5
Order By: Relevance
“…In vivo injections of anti-inflammatory doses of AnxA1 (26) led to IL-10 production in an ALXdependent manner, as demonstrated using a mouse colony deficient in the ortholog for the human receptor (4). Some evidence for a link between AnxA1 and IL-10 has been advanced in the literature using macrophages (27) and in models of gut injury (28). Our data provide molecular support to this pathway, linking the protein AnxA1-a master regulator of resolution (29)-and the cytokine IL-10 to ALX homodimerization.…”
Section: Discussionsupporting
confidence: 53%
“…In vivo injections of anti-inflammatory doses of AnxA1 (26) led to IL-10 production in an ALXdependent manner, as demonstrated using a mouse colony deficient in the ortholog for the human receptor (4). Some evidence for a link between AnxA1 and IL-10 has been advanced in the literature using macrophages (27) and in models of gut injury (28). Our data provide molecular support to this pathway, linking the protein AnxA1-a master regulator of resolution (29)-and the cytokine IL-10 to ALX homodimerization.…”
Section: Discussionsupporting
confidence: 53%
“…The clinical efficacy of anti-TNF therapy in IBD (3) supports this mechanism. Of interest, both PD1 n-3 DPA and RvD5 n-3 DPA did not regulate colonic levels of IL-10, setting these mediators apart from LXA 4 (28) or other proresolving mediators, like Annexin-A1 (29,30) and α-melanocyte stimulating hormone (31). To substantiate the physio-pathological impact of this new pathway, it was important to observe that inhibition of the enzyme responsible for conversion of DPA to DHA led to increased tissue levels of n-3 DPA-derived SPM, an effect linked to a reduction in systemic eicosanoid levels during I/R injury, supporting the host protective actions of these molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we investigated whether inhibiting AnxA1 in GILZ 2/2 mice could affect the phenotype of these mice. By using an AnxA1 neutralizing Ab previously used in other studies (15,22), we showed that mice in which AnxA1 was neutralized were refractory to resolution induced by Dex (Fig. 6C), indicating that by preventing the compensatory effects of AnxA1, GILZ 2/2 mice lost the ability to resolve inflammation in response to GC treatment.…”
Section: Anti-anxa1 Abolished Dex-induced Gilz Accumulationmentioning
confidence: 99%
“…To prevent the action of AnxA1 induced by Dex, mice were treated with anti-AnxA1 antiserum (0.1 ml hyperimmune serum diluted in 100 ml PBS/mouse, i.p.) (22). Nonimmune goat serum was used as control.…”
Section: Treatment Protocolsmentioning
confidence: 99%